The Knowledge and Adherence of Saudi Arabian Physiotherapists to Evidence-Based Practice Guidelines and Recommendations for the Treatment of Lateral Ankle Sprain (International Journal of Physiotherapy, 2025)
Background: The most common musculoskeletal injury to the lower extremities that occurs during sports and leisure activities is lateral ankle sprain (LAS). However, it appears that physiotherapists are using more non-evidence-based treatments. So, this study examined the knowledge and adherence of Saudi physiotherapists to the LASs’ clinical practice guidelines (CPGs) and recommendations.Methods: A questionnaire was used for this cross-sectional study. Two clinical examples, using the Ottawa Ankle Rules (OAR), were described: one positive (vignette II) and one negative (vignette I). The treatment that the physiotherapists would employ was described. The CPGs and recommendations were categorized as follows: partially followed, partially not followed, and not followed. Then, they used a 1-5 Likert scale to indicate their level of agreement with various CPG and guideline statements.Results: 386 physiotherapists (62.2% men and 37.8% women) completed the survey. Acute LAS with negative OAR was the clinical vignette. I. 2.07% of them reported "following" the recommended treatments, 39.64% "partially following,” 8.55% "partially not following, and 52.59% "not following." An acute LAS with positive OAR was the clinical vignette II, 5.18% of them reported "following" the recommended treatments, 18.65% "partially following" and 76.17% "not following". The statements for which a 70% consensus was attained were two statements (18.18%). The third and fifth statements were among those that the participants agreed upon, which were related to the assessment phase.Conclusion: The first-line suggested therapy for acute LAS management was unknown to the Saudi physiotherapists. Moreover, three-quarters of them were unable to recognize positive outcomes after radiation (OAR). The current findings highlight a gap between evidence and practice in LAS management.